2016
DOI: 10.24820/ark.5550190.p009.771
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated organic azides – their preparation and synthetic application

Abstract: Alkyl azides are widely used in many reactions. Although synthesis of such species is relatively well documented, fluorinated azides, especially with large perfluorinated or highly fluorinated groups, are sometimes tricky to make. The presence of fluorine in reacting molecules, sometimes causes significant changes in the reactivity of reacting species. In this paper we give a short overview of re-examination of currently available methods of synthesis of selected azides with highly fluorinated groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Thin-layer chromatography (TLC) and an MS analysis of the reduction of 1b with sodium borohydride provides evidence for the formation of p-amino benzyl alcohol, the product of water addition to the imine of p-quinone methide. The addition of sodium borohydride/copper (II) sulfate, a mixture known to reduce azides to amines [28], to 1c and 2c produces 89 and 92% N 2 O, respectively (Table 2). These results support Scheme 1 and suggest a reduction of the nitro and azide groups to the amine followed by decomposition to the Piloty's acid derivative.…”
Section: Compoundmentioning
confidence: 99%
“…Thin-layer chromatography (TLC) and an MS analysis of the reduction of 1b with sodium borohydride provides evidence for the formation of p-amino benzyl alcohol, the product of water addition to the imine of p-quinone methide. The addition of sodium borohydride/copper (II) sulfate, a mixture known to reduce azides to amines [28], to 1c and 2c produces 89 and 92% N 2 O, respectively (Table 2). These results support Scheme 1 and suggest a reduction of the nitro and azide groups to the amine followed by decomposition to the Piloty's acid derivative.…”
Section: Compoundmentioning
confidence: 99%
“…Evaporating the solvent by rotary evaporator to furnish hepta-Oacetyl-6'-O-azido-sucrose [6] (3.54g, 71%) as pure white crystals after recrystallization with ethyl alcohol. (Kamijo et al, 2015;Tomaszewska et al, 2017;Hosoya et al, 2019).…”
Section: Azidation Of Hepta-o-acetyl-6'-o-tosyl-sucrose [6]mentioning
confidence: 99%
“…The resulting organic azides are versatile compounds that provide an excellent starting point for the synthetic preparation of amines and the corresponding derivatives, nitrogen heterocycles, such as the extensively studied 1,2,3-triazoles, etc. 26,27 In our previous research, 28 we showed that HHDHs can be employed in the kinetic resolution of fluorinated aromatic epoxides, giving access to the corresponding enantioenriched or enantiopure fluorinated β-azido alcohols of synthetic relevance. Although HHDHs are potent biocatalysts, lower productivity on the preparative scale occurs as a result of chemical side reactions in the system.…”
Section: Introductionmentioning
confidence: 99%